2022
DOI: 10.1021/acs.analchem.1c04920
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Function Au–Ag-Stuffed Nanopancakes for SERS Detection, Discrimination, and Inactivation of Multiple Bacteria

Abstract: New strategies combining sensitive pathogenic bacterial detection and high antimicrobial efficacy are urgently desirable. Here, we report smart triple-functional Au–Ag-stuffed nanopancakes (AAS-NPs) exhibiting (1) controllably oxidative Ag-etching thickness for simultaneously obtaining the best surface-enhanced Raman scattering (SERS) enhancement and high Ag-loading antibacterial drug delivery, (2) expressive Ag+-accelerated releasing capability under neutral phosphate-buffered saline (PBS) (pH ∼ 7.4) stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Metal-based nanoarrays were considered as an ideal plasmonic substrate because of their favorable signal reproducibility and intense localized plasmon fields. Herein, based on our nanotechnology expertise, we fabricated uniform and ordered Au NAs as activated biosensors for HCC-related miR-224 detection. This biosensor realized the Raman/FL dual-modal detection based on the SERS and MEF mechanism and was integrated with the CHA amplification strategy for improving the sensitivity and reliability of detection.…”
Section: Resultsmentioning
confidence: 99%
“…Metal-based nanoarrays were considered as an ideal plasmonic substrate because of their favorable signal reproducibility and intense localized plasmon fields. Herein, based on our nanotechnology expertise, we fabricated uniform and ordered Au NAs as activated biosensors for HCC-related miR-224 detection. This biosensor realized the Raman/FL dual-modal detection based on the SERS and MEF mechanism and was integrated with the CHA amplification strategy for improving the sensitivity and reliability of detection.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Krishnan et al [ 76 ] synthesized bimetallic Ag@Au nanodisks, which showed greatly enhanced SERS performance with an enhancement factor up to 0.47 × 10 5 ( Figure 2 A). Zhou et al [ 77 ] reported smart triple-functional Au–Ag-stuffed nanopancakes (AAS-NPs) with multiple functions for bacteria sensing, inactivation in human blood samples and bacterial biofilm disruption ( Figure 2 B). SERS substrates made of magnetic nanocomposites can be used to separate and enrich target analytes in complex samples with the help of an external magnetic field, which not only achieves the pretreatment of complex matrix samples but also improves the SERS detection sensitivity of target analytes.…”
Section: Sers Substrates For Bacteria Detectionmentioning
confidence: 99%
“… ( A ) The preparation method for Ag@Au nanodisks as SERS substrate [ 76 ]. Reproduced with permission from American Chemical Society Copyright (2022); ( B ) SERS substrate made of smart, triple-functional Au-Ag-stuffed nanopancakes for discrimination, sensitive detection and inactivation of different pathogenic bacteria [ 77 ]. Reproduced with permission from American Chemical Society Copyright (2022); ( C ) SERS substrate made of magnetic-based, flower-like silver composite microspheres (Fe 3 O 4 @SiO 2 @Ag microflowers).…”
Section: Figurementioning
confidence: 99%
“…[ 125 ] Many different strategies have been developed for the detection of bacteria. [ 126 ] Currently, two different SERS techniques have been in use for bacterial detection. First is a label‐based SERS detection technique that uses SERS‐tags.…”
Section: Potential Applicationsmentioning
confidence: 99%